Customer Segmentation from a Supply Chain Service Perspective A Case Study at Volvo Penta - Gärdesmed, Mathilda; Koppel, Josefin (My University, 2019)
Several years ago, Volvo Penta experienced an expansion from serving one market with standardized products, towards a presence in two markets. This meant that the product variety increased and the customer needs became more complex. The standardized market allowed for one single set of supply chain services offered to all customers, in order to gain from economies of scale. However, due to the increased complexity of customer needs, Volvo Penta sees the possibility to develop a differentiated supply chain strategy in order to fulfill the customer needs and deviate from the current one-size-fits-all strategy. Therefore, this thesis aimed to propose a customer segmentation structure for Volvo Penta, in order to match different customer needs with supply chain services. Additionally, the study also aimed to examine how the customer segmentation could be made applicable to Volvo Penta. The proposed segmentation structure was accomplished by analyzing both segmentation processes and customer characteristics. Through analysis of segmentation processes, important knowledge of the impact from a segmentation for Volvo Penta was gained. Additionally, by analyzing different customer characteristics, an understanding of how to distinguish different customer needs was achieved. The analysis was based on findings from interviews, an internal questionnaire, and secondary data. During the study, three segmentation attributes were identified to have an impact on the customer need for supply chain services; product variation, business value, and purchasing pattern. By identifying two different levels for each attribute a segmentation structure was achieved. For each suggested customer segment, a set of services was proposed in order to fulfill the customer needs. The eight different segments were also branded in order to increase the applicability. With the segmentation, customers with different needs can be met with appropriate and beneficial supply chain services. Thereby, customer satisfaction and resource usage can be optimized. Additionally, from the proposed segmentation, Volvo Penta has now the opportunity to develop a differentiated supply chain strategy that both understands and manages different customer needs.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other industrial engineering and economics